Submandibular Push Exercise Using Visual Feedback from a Pressure Sensor in Patients with Swallowing Difficulties: A Pilot Study - Hwang, Jong-Moon (Healthcare (Basel), 2021)
Objectives: We aimed to determine the usefulness and effectiveness of a submandibular push exercise with visual feedback from a pressure sensor in patients with dysphagia through continuous exercise sessions. Methods: Twelve patients with dysphagia of various etiologies were included. A total of five exercise sessions (every 3 or 4 days) over three weeks were conducted. During the submandibular push exercise, patients were instructed to maintain a maximum force for 3 s, repeated for 1 min to measure the number of exercises, the maximum pressure, and the area of the pressure-time graph. We statistically compared the values of each exercise trial. Results: Among the 12 patients, eight completed the exercise sessions. As the number of exercise trials increased, the maximum pressure and the area in the pressure-time graph showed a significant increase compared to the previous attempt (p < 0.05). The maximum pressure and the area of the pressure-time graph improved from the first to the fourth session (p < 0.05). The values were maintained after the fourth session, and there was no significant difference between the fourth and the fifth exercise (p > 0.05). There was no significant difference between successful and non-successful groups, except for the Modified Barthel Index (p < 0.05). Conclusion: Through repetitive exercise training, the submandibular push exercise using visual feedback from a pressure sensor can be applied as an exercise method to strengthen swallowing related muscles, such as the suprahyoid and infrahyoid muscles. However, additional studies including more patients and a long-term study period are warranted to evaluate the effects of the exercise for improvement of dysphagia.